(untitled) (Journal of the College of Basic Education, 2022)
The importance of Creep property as a function of time and temperature is to study the ability of thermoplastics polymers under effect of environment conditions of use. In this research, Creep property has been studied to the (Polyethylene low density LDPE), which is used in the construction of farms covers and the bags for packing agricultural and industrial products for long periods, as were tests specifically measure the amount of strain per unit of time and calculate the Creep rate Ɛav for the following cases: At constant stress and temperature with variable of cross section area. It concluded that the creep rate inversely proportional to the sectional area when proven stress and temperature according to the weights. At constant cross section area and temperature with variable of stress. As noted in the low stress and having little effect on the rate of creep because of strained hardening, but with increasing stress get rapid elongation in the samples do not allow this type of hardening and increasing creep rate even tough the proven temperature and sectional area. At different temperature with constant stress and area cross section, concluded that polyethylene-LD has a plastic behavior as long as the temperature is higher than the temperature of Glass Transition temperature (Tg).